Macroeconomic Sensitivity and Capital Structure Effects on Defensive Stock Valuation: Evidence from PT HM Sampoerna Tbk (2013–2024) - Sari, D. Sintiani Novita (Yayasan Pendidikan Penelitian Dan Pengabdian Al-amsi, 2025)
This study investigates the macroeconomic sensitivity and capital structure effect on stock valuation within a defensive industry context. Using annual time-series data from 2013–2024, this research examines the influence of inflation and the Debt-to-Equity Ratio (DER) on the stock price of PT HM Sampoerna Tbk. Employing multiple linear regression with classical assumption diagnostics, the findings reveal that inflation exerts a positive and statistically significant effect on stock price (? = 10,553.368; p < 0.05), while DER shows no significant influence. The model explains 31.9% of stock price variation (Adjusted R² = 0.319). The results suggest that in industries characterized by inelastic demand and strong pricing power, inflation may function as a value-supporting factor rather than a risk signal. This study extends capital structure and macro-finance literature by demonstrating context-dependent inflation effects in emerging defensive markets.